Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was wondered how to find the function in this equality:

$f(f(x))=2x$. Also $f$ is continuous.

I don't need the answer, how to find it is more important.

share|cite|improve this question
I do not know all the solutions to this functional equation. But as a start, since the right hand side is linear, did you try functions of the form $f(x) = ax + b$? (Added: $\pm \sqrt{2}x$ are both solutions.) – Srivatsan Sep 20 '11 at 15:14
Some useful(?) observations: $f$ is bijective. By continuity, it is strictly monotonic. Wlog we can assume that $f$ is increasing because if $f$ is a solution, then so is $-f$. I can show $f(0) = 0$. (Proof: $f^2(f(0)) = 2f(0)$, but $f(f^2(0))=f(2 \cdot 0) = f(0)$. Comparing the two expressions, $f(0)=0$.) – Srivatsan Sep 20 '11 at 15:20
See the application section for Schoeder's equation. It goes by constructing function $\Psi$ such that $\Psi(2 x) = s \Psi(x)$ for some $s$, e.g. $\Psi(y) = y$ and $s=2$. Now $f(x) = \Psi^{-1}( \sqrt{s} \Psi(x)) = \sqrt{2} x$. – Sasha Sep 20 '11 at 15:22
Apply $f$ to both sides and you find that $2f(x)=f(2x)$. – alex.jordan Sep 20 '11 at 15:23
It's not true that if $f$ is a solution, so is $-f$. – Robert Israel Sep 20 '11 at 17:03
up vote 10 down vote accepted

If $f$ has a power series, you could try composing the power series. Since $f(0)=0$, we don't need to translate: $$ f(x) = a_1x+a_2x^2+a_3x^3+\dots $$ Therefore, $$ \begin{align} f(f(x)) &= a_1(a_1x+a_2x^2+a_3x^3+\dots)\\ &+a_2(a_1x+a_2x^2+a_3x^3+\dots)^2\\ &+a_3(a_1x+a_2x^2+a_3x^3+\dots)^3\\ &+\dots\\ &=a_1^2x+a_1a_2(1+a_1)x^2+a_1(2a_2^2+a_3+a_1^2a_3)x^3+\dots\tag{1} \end{align} $$ Using $(1)$, we get that $a_1=\sqrt{2}$ or $a_1=-\sqrt{2}$, then $a_2=0$, and $a_3=0$. Checking, we see that both $f(x)=\sqrt{2}\;x$ and $f(x)=-\sqrt{2}\;x$ work.

Addition: Using alex.jordan's comment that $f(2x)=2f(x)$, if $f^{\;\prime}\in\operatorname{Lip}(\alpha)$ for some $\alpha>0$, i.e. $f\in\operatorname{Lip}(1+\alpha)$, then these two solutions are the only solutions.

share|cite|improve this answer
Vahid is right. – Rok Kralj Sep 20 '11 at 15:55
Look at Srivatsan's second comment: we have $f(f(f(0)))=2f(0)=f(0)$ since $f(f(0))=0$. – Davide Giraudo Sep 20 '11 at 16:06
@Vahid You can also get $f(0)=0$ from alex.jordan's comment directly. $f(0) = f(2 \cdot 0) = 2f(0) \implies f(0)=0$. – Srivatsan Sep 20 '11 at 16:36
@Davide: Thanks. I was assuming people had seen that, but I guess I should have mentioned it explicitly. – robjohn Sep 20 '11 at 16:42
@robjohn:without f(0)=0 your proof can be corrected with alittle changes. – Vahid Sep 20 '11 at 19:52

For another class of solutions, try $f(x) = -c x$ for $x \ge 0$, $-(2/c) x$ for $x < 0$, where $c > 0$ is constant. Still more generally, let $h(x) = x p(\log_2(x))$ for $x > 0$ where $p$ is continuous and periodic with period 1 and $p(t) + p'(t)/\ln(2) > 0$ everywhere. Thus $h$ is an increasing continuous function from $(0,\infty)$ onto itself, thus invertible on $(0,\infty)$. Let $f(x) = - h(x)$ for $x > 0$, $f(0) = 0$, $f(x) = 2 h^{-1}(-x)$ if $x < 0$.

share|cite|improve this answer
If I understand correctly, in particular, you are able to give examples for $f$ that are differentiable everywhere but at the origin. Am I right? – Srivatsan Sep 20 '11 at 18:25
Yes, you're right. – Robert Israel Sep 20 '11 at 18:58
These are the solutions I was excluding when I said that $\sqrt{2}x$ and $-\sqrt{2}x$ are the only solutions in $\operatorname{Lip}(1+\alpha)$. (+1) – robjohn Sep 20 '11 at 21:33

Nevermind! I became focused on solving $f(2x)=2f(x)$, which is a consequence of the original equation, but not equivalent. I'll leave this here in case it helps with an actual solution.

As has been noted, $f(0)=0$. Let $f(1)=a$.

As noted in my comment, $$f(2x)=2f(x)$$ Inductively, for all $n\in\mathbb{Z}$, $$f(2^nx)=2^nf(x)$$ In particular, $f(2^n)=2^na$. That is, upon choosing a value $a$ for $f$ at $1$, the function's values at $\{\ldots,\frac14,\frac12,1,2,4,\ldots\}$ are immediately determined.

Now I claim that any continuous function on $[1,2]$ with $f(1)=a$ and $f(2)=2a$ extends to a function $f$ on $(0,\infty)$, using the relation $f(2^nx)=2^nf(x)$.

Similalary,we could choose a completely different continuous function on $[-2,-1]$ with $f(-1)=b$ and $f(-2)=2b$, and extend to $(-\infty,0)$. Combined with the observation that $f(0)=0$, this gives a very big space of solutions defined on $(-\infty,\infty)$.

As an example of how exotic these solutions could be, consider $f(x)=(\sin(2\pi\log_2(x))+5)x$.

share|cite|improve this answer

More generally, suppose we want to find a "composition square root" of $ax^b$, where $a$ and $b$ are positive real numbers. Let's assume there is a solution of the form $f(x)=cx^d$ for some real numbers $c$ and $d$ and see where that takes us. From $f\left(f(x)\right) = ax^b,$ we get

$$c \cdot \left(cx^{d} \right)^{d} \; = \; ax^{b}$$

Therefore, $c^{d+1}=a$ and $d^{2}=b$, which we can easily solve for $c$ and $d$ in terms of $a$ and $b$ to get

$$f(x) \; = \; a^{\frac{1}{{\sqrt b}\; +\; 1}} \cdot x^{\sqrt b}$$

share|cite|improve this answer

This is not a general solution, but I think there are more continuous solution the functional equation. Consider, for e.g.,

$$ f(x) = \begin{cases} x \left( \frac{11}{6} - \frac{x}{3} \right), &\text{ for } x \in \left[ 1, \frac{3}{2} \right], \\ \frac{11}{2} - \sqrt{\frac{121}{4} - 12x}, &\text{ for } x \in \left[ \frac{3}{2}, 2 \right], \end{cases} $$

We can extend the definition to all positive numbers by declaring: $$ f(x) = \begin{cases} \frac{1}{2}f(2x), & \ 0 < x < 1, \\ 2f \Big(\frac{x}{2} \Big), & \ x > 2, \end{cases} $$

Finally, we extend the function to negative numbers and zero, by declaring the function to be odd. So $f(0) = 0$ and $f(-x) = -f(x)$ for all $x > 0$.

If I haven't done any mistakes, then this function is continuous and satisfied $f(f(x)) = 2x$.

We should check that the function is continuous, and it satisfies $f(f(x)) = 2x$. I am not spelling out the details here now, because it is quite tedious :-). I will think whether is a direct way to verify our requirements. Meanwhile, if there's any demand to show specific properties, I can certainly do so.

share|cite|improve this answer
Or take any continuous increasing function $f$ from $[1,b]$ onto $[b,2]$ where $1 < b < 2$, define $f(t) = 2 f^{-1}(t)$ on $[b,2]$, and extend... – Robert Israel Sep 20 '11 at 17:50
@Robert That's exactly what I tried to do. :-) I wasn't sure about whether any generic construction like that works or some additional assumption must be made. The basic issue is that we don't get continuity for free at $1$ and $b$; one has to tweak. – Srivatsan Sep 20 '11 at 18:19
I don't see what tweaking is needed. If the original $f$ is continuous from $[1,b]$ onto $[b,2]$ with $f(1) = b$ and $f(b) = 2$, then after extending, $f(1-) = (1/2) f(2-) = f^{-1}(2-) = b$. Also, $f(b+) = 2 f^{-1}(b+) = 2$. – Robert Israel Sep 20 '11 at 19:17
@Robert I think you are right. I am mistaken somehow. I will think about it for some more time to convince myself fully. – Srivatsan Sep 20 '11 at 19:23

There are many constructions already of continuous functions satisfying the hypothesis. Even better, I believe that Robert gives examples where the function is differentiable everywhere in $\mathbb R \setminus \{0\}$. I will show that this situation is tight.

In particular, I show that if $f$ is such that

  1. $f(f(x))=2x$, and
  2. $f$ is differentiable at $0$,

then $f(x) = cx$ for all $x$, where $c := f'(0)$. Note that we do not require continuity anywhere but at the origin. Moreover, substituting $f(x)=cx$ in the functional equation, it is clear that the only possible values of $c$ are $\pm \sqrt{2}$.

We have already showed that $f(0) = 0 = c \cdot 0$, so fix $t \in \mathbb R \setminus \{0\}$. Define the sequence $x_n$ by $x_n := \frac{t}{2^n}$. Then from alex.jordan's observation that $f(2x) = 2f(x)$, it is evident that the sequence $$ \frac{f(x_n)}{x_n} = \frac{f(t)}{t} $$ for all $n$. In particular, the limit is the above expression as well.

On the other hand, notice that $x_n \to 0$, and by hypothesis $f'(0) = c$. Therefore, $$ \frac{f(t)}{t} = \lim_{n \to \infty} \frac{f(x_n)}{x_n} = \lim\limits_{n\to \infty} \frac{f(x_n) - f(0)}{x_n} = \lim\limits_{x\to 0} \frac{f(x) - f(0)}{x} = f'(0) = c, $$ which gives the claim.

share|cite|improve this answer

$f$ is injective. Assume that $f(x) = f(y)$ for some $x \neq y$, then $2x = f(f(x)) = f(f(y)) = 2y$. As $f(\mathbb{R}) = \mathbb{R}$ by definition, $f$ is surjective and hence bijective. $f$ is also monotonous.

From here on I'd like to follow up alex.jordan's answer.

From $f(1) = a$ we get $f(a) = 2$, another necessary condition. For $a \geq 0$, three cases are possible:

  1. $1 < a < 2$
  2. $0 < a \leq 1$ ($a=0$ is not possible)
  3. $a \geq 2$

For case 1., I claim that any continuous and bijective function $f$ with the following properties solves the assignment:

  1. $f(0)=0, f(1)=a, f(a)=2, f(2)=2a$
  2. For $x \in (1, a)$, $f(x) \in (a, 2)$ so that $f(f(x)) = 2x \in (2, 2a)$.
  3. (from alex.jordan's answer): $f(2^n x) = 2^n f(x)$.
  4. (from alex.jordan's answer): Likewise for $x < 0$ with $f(-1) = b$ and $f(-2) = 2b$.

Informally speaking, any deviation from $f(x) = ax$ imposed by the first application of $f$ is undone by its second application. IMO, this is more restrictive than the solution provided by alex.jordan. Moreover, I believe that the above conditions are necessary as well: 1., 3. and 4. have been proven necessary by alex.jordan, 2. is necessary due to bijectivity and monotony which has been proven necessary above.

Case 2. is impossible: $a \leq 1 < 2$, but $f(a) \geq f(2) > f(1)$.

Case 3. is impossible, too: $1 < 2 \leq a$, but $f(a) \leq f(1) < f(2)$.

A similar, but much more convoluted solution is possible for the case $a < 0$, yielding $-2 < a < -1$. Here, $f((1, -a)) = (b, -2)$, and $f((b, -2)) = (2, -2a)$; likewise, $f((-a, 2)) = (-2, 2b)$ and $f((-2, 2b)) = (4, -4a)$.

$f(x) = \pm \sqrt{2} x$ are special cases of the above generic solution.

Edit: Now I see that this has been proposed by Robert Israel before.

share|cite|improve this answer
Comments, anyone? – krlmlr Sep 26 '11 at 8:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.